Effective burnout prevention strategies for counsellors and other therapists: a systematic review and meta-synthesis of qualitative studies - Duncan S; Pond R (Informa UK Limited, trading as Taylor & Francis Group., 2024)
Therapists are susceptible to burnout and need strategies to prevent it. This systematic review and meta-synthesis of qualitative literature examined what practicing therapists (including counsellors, psychotherapists, and psychologists) report being helpful in preventing and minimising burnout. A search by EBSCO Discovery Service across all major article databases and a complementary search using Google Scholar led to the identification of nine eligible studies (with 542 therapists). Studies were critically appraised, data were extracted, and findings synthesised using thematic analysis. Nine themes/helpful factors for preventing burnout in the therapeutic profession were identified: time off, leisure activities, exercise, perspective (having a particular mindset or attitude towards the role), support and connections, boundaries and balance, awareness/mindfulness of one’s internal state and the impact of work, spirituality/meditation, and professional growth and self-use of clinical approaches. Information about these strategies needs to be included and practised during therapist training programmes. Future research needs to investigate culturally preferred strategies for preventing burnout. Importantly, while practitioners are responsible for implementing self-care strategies for their well-being, it is critical that organisations take an active role in burnout prevention by putting policies in place, providing training to increase awareness of burnout, and supporting staff to manage pressures they face.
Keywords: Burnout prevention; counselling; herapists; systematic review; self-care